The Role of Gamification in Digital Workforce Training: A Case Study of Knowledge Retention and Engagement in Cloud Computing Training Course - Krismassion Prihationo; A. Sobandi (Eduvest - Journal of Universal Studies, 2025)
Indonesia’s Digital Talent Scholarship (DTS) program aims to enhance digital workforce readiness but struggles with sustaining engagement and knowledge retention in online training. While gamification (e.g., badges, leaderboards) has shown promise in education, its effectiveness in professional training and across diverse regional contexts remains unclear. This study examines how gamification elements influence engagement and retention in DTS’s Cloud Computing course, while assessing regional variations in outcomes. A quasi-experimental design compared 1,200 participants (gamified vs. standard LMS groups) using pre/post-tests, ANOVA, and regression analyses. Data included engagement surveys, retention tests, and demographic questionnaires. Engagement levels were consistent across provinces, but retention varied significantly, with weak correlations between gamification elements and outcomes. Regional disparities suggested contextual factors (e.g., resources, culture) outweighed gamification’s direct impact. The study underscores the need for context-sensitive gamification strategies tailored to regional and cultural differences, challenging one-size-fits-all approaches. It calls for future research on longitudinal effects, qualitative insights, and narrative-driven gamification to optimize professional training.